Photosynthetic Paramaters of Two Indonesian Soybean Top Varieties - Padjung, Rusnadi; Syam'un, Elkawakib; Kasim, Nurlina (AGRIVITA, Journal of Agricultural Science, 2021)
Each plant genotype has its own photosynthetic parameters required to run crop growth model. The research is aimed to characterize photosynthetic parameters particularly maximum photosynthesis and initial light use efficiency of two soybean varieties widely planted in Indonesia, Dena-1 and Anjasmoro. Photosynthetic performances were measured in a designed experiment to study the effect of Actinomycetes spp. on growth and yield of soybean. Photosynthesis was measured using an open chamber portable photosynthetic system (LI-6400), at variable Photosynthetically Active Radiation (PAR), i.e. 500; 1,000; 1,500; and 2,000 µmol (photon)/m2/s. The photosynthetic light response curve (PN/I curve) was developed using Solver function of Microsoft Excel. Maximum gross photosynthesis (Pgmax) of Dena-1 is 45.64 μmol (CO2)/m2/s, while Anjasmoro variety is only 34.81 μmol (CO2)/m2/s. Quantum yield at low light (initial light use efficiency) of Dena-1 is also higher with the value of 0.068 μmol (CO2)/μmol(photons) compared to Anjasmoro that have 0.058 μmol (CO2)/μmol (photons). Hence light response curve of Dena-1 variety is consistently higher than Anjasmoro. Under Actinomycetes spp. treatment the light response curve of Dena-1 is higher than Anjasmoro at PAR lower than 706 μmol (photon)/m2/s and higher at PAR above it.